Penerapan Media Poster Digital Berbasis Project Based Learning Terintegrasi Tri-N Untuk Meningkatkan Keaktifan Belajar Pendidikan Pancasila - Firdausia, Luftia; Wibawa, Sutrisna (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2024)
AbstractThis research aims to determine the application of digital poster media based on the Tri-N integrated Project Based Learning model on students' active learning in Pancasila Education subjects in 4th of Karangnongko 1 State Elementary School. This research is descriptive qualitative research. The subjects of this research were 4th students. Data collection techniques in this research were carried out using interviews, observation, questionnaires, and documentation. The data analysis techniques used in this research are data reduction, data display, and drawing conclusions. The importance of implementing the Tri-N integrated Project Based Learning model with digital poster media means that students have no difficulty in asking, answering and thinking activities. The research results based on interviews with teachers say that students are more active with the application of digital poster media based on the Tri-N integrated Project Based Learning model. Based on the research results, it can be seen that the application of digital poster media based on the Tri-N integrated Project Based Learning model can increase student learning activity in Pancasila Education subjects. The teacher made the digital poster media entitled